Basic electronics - Holbrook, Harold D. (Pergamon Press, 1971)
Basic Electronics is an elementary text designed for basic instruction in electricity and electronics. It gives emphasis on electronic emission and the vacuum tube and shows transistor circuits in parallel with electron tube circuits. This book also demonstrates how the transistor merely replaces the tube, with proper change of circuit constants as required. Many problems are presented at the end of each chapter. This book is comprised of 17 chapters and opens with an overview of electron theory, followed by a discussion on resistance, inductance, and capacitance, along with their effects.